An 18 gene expression-based score classifier predicts the clinical outcome in stage 4 neuroblastoma. Issue 1 (December 2016) - Formicola, Daniela; Petrosino, Giuseppe; Lasorsa, Vito; Pignataro, Piero; Cimmino, Flora; Vetrella, Simona; Longo, Luca; Tonini, Gian; Oberthuer, André; Iolascon, Achille; Fischer, Matthias; Capasso, Mario
Abstract Background The prognosis of children with metastatic stage 4 neuroblastoma (NB) has remained poor in the past decade. Patients and methods Using microarray analyses of 342 primary tumors, we here developed and validated an easy to use gene expression-based risk score including 18 genes, which can robustly predict the outcome of stage 4 patients. Results This classifier was a significant predictor of overall survival in two independent validation cohorts [cohort 1 (n = 214):P  = 6.3 × 10−5 ; cohort 2 (n = 27):P  = 3.1 × 10−2 ]. The prognostic value of the risk score was validated by multivariate analysis including the established markers age andMYCN status(P  = 0.027). In the pooled validation cohorts (n = 241), integration of the risk score with the age and/orMYCN status identified subgroups with significantly differing overall survival (ranging from 35 to 100 %). Conclusion Together, the 18-gene risk score classifier can identify patients with stage 4 NB with favorable outcome and may therefore improve risk assessment and treatment stratification of NB patients with disseminated disease.